Moderators of the effect of psychological interventions on depression and anxiety in cardiac surgery patients: A systematic review and meta-analysis - Protogerou, C.; Fleeman, N.; Dwan, K.; Richardson, M.; Dundar, Y.; Hagger, Martin (2015)
Cardiac surgery patients may be provided with psychological interventions to counteract depression and anxiety associated with surgical procedures. This systematic review and meta-analysis investigated whether intervention efficacy was impacted by type of cardiac procedure/cardiac event; control condition content; intervention duration; intervention timing; facilitator type; and risk of bias. MEDLINE, EMBASE, and PsycINFO were searched for randomized controlled trials comparing anxiety and depression outcomes, pre and post psychological and cardiac interventions. Twenty-four studies met the inclusion criteria for the systematic review (N = 2718) and 16 of those were meta-analysed (N = 1928). Depression and anxiety outcomes were reduced more in interventions that lasted longer, were delivered post-surgery, and by trained health professionals. Depression (but not anxiety) was reduced more when the experimental intervention was compared to an ‘alternative’ intervention, and when the intervention was delivered to coronary artery bypass graft patients. Anxiety (but not depression) was decreased more when interventions were delivered to implantable cardioverter defibrillator patients, and were of ‘high’ or ‘unclear’ risk of bias. In addition to estimating efficacy, future work in this domain needs to take into account the moderating effects of intervention, sample, and study characteristics.